Digital transformation with Vietnamʼs entrepreneurial communities in a globalization context - Dinh, Thu Ha; Le, Thuy Anh; Phan, Minh Duc (Луцьк : Вежа-Друк, 2023)
In the context of current globalization, digital transformation (DT) plays an important role for businesses to be able to compete and survive in the international market. Through the application of digital technology, businesses can optimize production and management processes, improve customer access, and improve competitiveness, creating new business opportunities and potential revenue growth. However, by 2022, Vietnamese businesses have made strong progress in DT. In most operational areas, Vietnamese enterprises are in the middle of the "developed" stage and are increasingly approaching the "advanced" level of DT, which means they have begun to develop plans for the digitization although implementation of digitization is still fragmented and many processes have not been automated. Recognizing the achievements and limitations in the DT process at Vietnamese enterprises, and in the context that DT is an inevitable and objective trend globally, the research team selected the topic “Digital Transformation with Vietnamʼs Entrepreneurial Communities in a Globalization Context” for in-depth research. This study will analyze the current situation of DT in Vietnamese enterprises, assess the strengths and weaknesses of Vietnamese enterprises in the DT process. From there, the team will propose a number of recommendations to improve the efficiency of DT in Vietnamese enterprises. With the results obtained, the study can be a reference for countries pursuing the goal of DT, specifically for Ukraine.
Keywords: digital transformation; developed; Vietnamʼs entrepreneurial communities; F68; O33; O38; O53; M15